Recognition and Application of the Law and Official Documents of Unrecognized States (International Private-Law Problems) - Haykyants, A. (Bulletin of Yerevan University C: Jurisprudence, 2019)
The number of unrecognized states is growing: currently, their number is close to two hundred. Only in the post-Soviet space, six unrecognized states were formed. Unrecognized states are actively involved in integration processes. Moreover, economic, humanitarian, and cultural ties are developing with them, but there are still some problems along the way, including those of legal nature. The main legal problem refers to the international legal personality of unrecognized states. The constitutive, declarative and compromise theories are analyzed in detail in the paper presented with a special emphasis on the declarative theory.